Phase 2 study of parsaclisib (INCB050465), a highly selective, next-generation PI3Kδ inhibitor, in relapsed or refractory diffuse large B-cell lymphoma (CITADEL-202). Issue 2 (28th January 2021) - Coleman, Morton; Belada, David; Casasnovas, René-Olivier; Gressin, Rémy; Lee, Hui-Peng; Mehta, Amitkumar; Munoz, Javier; Verhoef, Gregor; Corrado, Claudia; DeMarini, Douglas J.; Zhao, Wanying; Li, Jia; et al.
Abstract: Parsaclisib, a potent, highly selective, next-generation PI3Kδ inhibitor, was evaluated as monotherapy in CITADEL-202 (NCT02998476), an open-label, multicenter, phase 2 study in patients with relapsed or refractory diffuse large B-cell lymphoma. Patients enrolled into 2 groups (A, Bruton tyrosine kinase [BTK] inhibitor naïve, n  = 55; B, BTK inhibitor experienced, n  = 5) received oral parsaclisib 20 mg once daily for 8 weeks, then 20 mg once weekly while deriving benefit. The futility boundary was crossed at the interim analysis of Group A, resulting in a negative study. Parsaclisib monotherapy demonstrated an objective response rate (ORR) of 25.5% (8 complete metabolic responses/6 partial metabolic responses) and a median duration of response of 6.2 months. ORR in Group B was 20.0% (1 complete metabolic response). Parsaclisib monotherapy demonstrated manageable toxicities with no new safety signals reported. Further evaluation of parsaclisib in combination with standard therapies and active investigational agents is underway.